Inhibition of Nitrate Uptake by Ammonium in Barley. Analysis of Component Fluxes - Kronzucker, Herbert J. (American Society of Plant Physiologists, 1999)
NO(3)(−) uptake by plant roots is rapidly inhibited by exposure to NH(4)(+). The rapidity of the effect has led to the presumption that the inhibition results from the direct effects of NH(4)(+) at the plasma membrane. The mechanism of this inhibition, however, has been in contention. In the present study we used the radiotracer (13)N to determine the relative effects of short-term exposures to NH(4)(+) on the (13)NO(3)(−) influx, efflux, and partitioning of absorbed (13)N in barley (Hordeum vulgare) roots. Plants were grown without NO(3)(−) or NO(2)(−) (uninduced for NO(3)(−) uptake), or with 0.1, 1.0, 10 mm NO(3)(−), or 0.1 mm NO(2)(−) (to generate plant roots induced for NO(3)(−) uptake). Exposure to 1 mm NH(4)(+) strongly reduced influx; the effect was most pronounced in plants induced for NO(3)(−) uptake when NO(3)(−) absorption was measured at low external NO(3)(−). At higher [NO(3)(−)] and in uninduced plants the inhibitory effect was much diminished, indicating that NH(4)(+) inhibition of influx was mediated via effects on the inducible high-affinity transport system rather than on the constitutive high-affinity transport system or the low-affinity transport system. Exposure to NH(4)(+) also caused increased NO(3)(−) efflux; the largest effect was at low external [NO(3)(−)] in uninduced plants. In absolute terms, the reduction of influx made the dominant contribution to the observed reduction of net uptake of NO(3)(−). Differences in response between plants induced with NO(3)(−) and those induced with NO(2)(−) indicate that NO(2)(−) may not be an appropriate analog for NO(3)(−) under all conditions.